Cytological grading of breast carcinomas correlating with ultrasonographic findings, histopathologic grade and Her2neu oncogene status in women of age group thirty to sixty five years - Ena Dowerah; K L TaLukdar (Wolters Kluwer Medknow Publications, 2013)
Background: Breast cancer is a malignant disease with a heterogeneous prognosis. It is the most common cancer in the urban Indian population. Women over 30 years of age are especially prone to develop this type of cancer. There are various prognostic factors that have been studied in invasive ductal carcinomas to predict the tumour behaviour. As fine needle aspiration cytology is an important investigation for diagnosis and grading of the tumour, preoperative evaluation of the tumour behaviour can be studied. Aim : The aim of the study was to diagnose and grade the tumours cytologically by fine needle aspiration cytology (FNAC), to study the tumour behaviour by ultrasonography, by histo pathological examination and also to study the her2neu oncogene overexpression of the malignant tumours. Materials & methods: The present study was carried out in Gauhati Medical College, Guwahati, Assam from May, 2010 to July, 2012. The patients presenting with breast lumps were selected for the study. FNAC smears were stained by Papaniculaou and May Grunwald Giemsa stain. Ultrasonography of the breast lumps were done. Histopathological examination was done using the H & E stain. Immuno- histochemical study was done to know the her2neu oncogene overexpression by the tumours. Results & observations : The age of patients with malignant tumours were found in the pre and perimenopausal age group. 48% of the malignant tumours were infiltrating duct carcinoma and of high grade. Her2neu overexpression was seen in 35% of the malignant tumours. Conclusion: A good correlation exists between the cyto-histopathologic grade of the tumours (85.3%), BIRADS 5 category on ultra sonography with histopathologic grade (98.5%) and her2neu oncogene overexpression along with histopathologic grade (93.3%). Therefore, cytological grading indicates an important prognostic marker to know the behaviour of breast carcinomas.